Myotonic Dystrophy-1 Complicated by Factor-V (Leiden) Mutation - Josef Finsterer; Claudia Stöllberger (Case Reports in Medicine, 2015)
Objectives. Presence of a factor-V Leiden mutation in a patient with myotonic dystrophy type 1 (DM1) has been reported only once. Here we report the second DM1 patient carrying a factor-V mutation who died from long-term complications of this mutation. Case Report. A 66-year-old DM1 patient with multi-organ-disorder syndrome developed a first deep venous thrombosis (DVT) and consecutive pulmonary embolism (PE) at age 50 y. Acetyl-salicylic acid was given. One year later he experienced a second DVT; that is why phenprocoumon was started. Despite anticoagulation, he experienced a third DVT bilaterally and a second PE bilaterally at 61 y; that is why a vena cava filter was additionally deployed. Despite therapeutic anticoagulation, he experienced a vena cava filter thrombosis at age 62 y. Genetic workup revealed a heterozygous factor-V mutation in addition to a CTG-repeat expansion of 500. As a consequence of PE he developed chronic obstructive pulmonary disease and experienced recurrent pulmonary infections, which were lastly responsible for decease at age 66 y despite intensive care measures. Conclusion. The heterozygous Leiden mutation may severely affect DM1 patients to such a degree that they die from its complications. If DM1 patients present with unusual manifestations, search for causes other than a CTG-repeat expansion is indicated.